Occurrence and susceptibility of yeasts present in the polluted waters of Dilúvio Stream, Porto Alegre, Brazil - Iwanczuk, Kimberly; Feltrin, Thaisa; Minotto, Elisandra; Bucker, Francielle; Milagre, Luciana; Van Der Sand, Sueli Teresinha (Revista Brasileira de Biociências, 2019)
Water is one of the naturally occurring essential requirements of all life functions. Today water pollution has become one of the major problems for all life forms. Dilúvio Stream is one of the main watercourses in Porto Alegre, Brazil and receives domestic and hospital sewage and rain waters, which favors the growth of microorganisms. This study investigates the presence of yeasts in water samples collected from Dilúvio Stream and assesses virulence factors and the susceptibility of antifungal agents commonly prescribed for the treatment of mycoses. Samples were collected at three sites, in two seasons of the year, seeded and isolated in different culture media supplemented with chloramphenicol. Biochemical assays, thermotolerance at 37ºC, proteinase, and phospholipase activities were carried out to identify isolates. Tests to determine resistance to antifungal included a susceptibility test and minimum inhibitory concentration (MIC) evaluation using different antifungal agents. Results showed that Ascomycota prevailed among the isolates and that 25% of which were potentially opportunistic yeasts. The susceptibility test revealed that the isolates were resistant to fluconazole and voriconazole, while the minimum inhibitory concentration test showed resistance to fluconazole and to itraconazole.